2001
DOI: 10.1021/bp010020k
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Culture of Immobilized Streptomyces Cells for Kasugamycin Production

Abstract: Continuous cultures of immobilized Streptomyces kasugaensis, a kasugamycin producer, were carried out on Celite beads. When using a prototype separator for immobilized-cell separation and recycling, the continuous operation could not be sustained for an extended period as a result of an excessive loss of immobilized cells caused by the poor performance of the separator. Accordingly, the immobilized-cell separator was revised to provide better immobilized-cell settling and thus recycling into the reactor. In a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…operates at several layers of control. This involves a complex regulatory network in response to external stimuli, such as nutrient depletion, salt shock, oxidative stress and acidic pH shock [8,14,17,18,26]. Some of these aVect only one speciWc antibiotic production, whereas others aVect several antibiotic productions along with morphological diVerentiation, suggesting that the two processes share some elements of genetic control, while others are unique.…”
Section: Introductionmentioning
confidence: 99%
“…operates at several layers of control. This involves a complex regulatory network in response to external stimuli, such as nutrient depletion, salt shock, oxidative stress and acidic pH shock [8,14,17,18,26]. Some of these aVect only one speciWc antibiotic production, whereas others aVect several antibiotic productions along with morphological diVerentiation, suggesting that the two processes share some elements of genetic control, while others are unique.…”
Section: Introductionmentioning
confidence: 99%
“…In one of our previous studies to investigate pH shock effects on secondary metabolites production, more than 7-fold enhancement in kasugamycin production in a bioreactor culture of S. kasugaensis was observed when an artificial pH drop and recovery was introduced [7,8]. In another case, it was found that an acidic pH shock caused earlier initiation of stationary phase, enhanced the biosynthesis of secondary metabolites, and activated the major metabolic pathways in surface grown cultures of S. coelicolor A3(2) [9].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a cell immobilization method effective in achieving high cell or biocatalyst density (1,12) and a novel bioreactor design apt for dealing with a multiphase liquid mixture were proposed for the development of an efficient bioreactor system for diesel desulfurization. The performance of the newly developed immobilized-cell reactor system was investigated in a series of repeated batch experiments at various carbon source concentrations and oil-to-water phase ratios.…”
Section: Introductionmentioning
confidence: 99%